Unraveling Board Gender Dynamics and Firm PerformanceInsights from The Indian IT Sector - Kaur , Sukhjinder; Kang , Dr. Lakhwinder Singh (International Journal of Accounting and Economics Studies, 2025)
This research work attempts to investigate how gender diversity affects operational outcomes within India’s Information Technology (IT) sector. ‎The study specifically focuses on the roles of women independent directors and women holding multiple directorships, as outlined by the ‎Companies Act of 2013. This study also accounts for governance and firm-specific attributes to evaluate the influence of gender-diverse boards, ‎women independent directors, and women occupying several board positions on the market value of Indian IT companies listed on the BSE ‎Information and Technology Index. The analysis spans a period of ten years from 1st April 2013 to 31st March 2023, using the Generalised ‎Method of Moments (GMM) as the dynamic panel data estimation technique, which combines level and difference equations to address ‎endogeneity issues. The findings indicate a substantial positive link between the diversity of gender on boards and business performance, ‎underscoring the value of diverse perspectives in enhancing governance and strategic outcomes. Conversely, the presence of independent ‎women directors is inversely related to business performance, suggesting potential tokenism and cultural constraints that may limit their ‎influence. In contrast, women holding multiple directorships positively contribute to firm performance by enhancing board effectiveness and ‎strategic input. This study is limited to the IT sector, and the unique socio-cultural and regulatory environment in India may constrain the cross-contextual applicability of the findings across divergent industry verticals or geographic domains. Nevertheless, this research serves as a ‎valuable contribution to the limited studies available on gender diversity in corporate governance within the Indian IT sector and is among the ‎first to delve into the distinct roles of women independent directors and multiple directorship holders in a highly competitive and dynamic ‎industry‎.